Urban Land Acquisition and Involuntary Resettlement : Linking Innovation and Local Benefits - Roquet, Vincent (World Bank Group, Washington, DC, 2015)
With rapid urbanization and an increasing number of publicly-funded urban projects, there is a growing demand to address complex land acquisition and involuntary resettlement issues in urban settings. A variety of major urban projects in areas such as urban development, renewal or upgrading, urban transport, urban watershed management, water supply and sanitation, and urban solid waste management require substantial land acquisition and resettlement efforts that raise significant risks to people and investments. Governments and international financing institutions must identify these risks early and manage them adequately.